Regulation of technical standards of digital radiography: literature review; Неразрушающий контроль: электронное приборостроение, технологии, безопасность; Т. 2 - Strugovtsov D. V. (Electrical Engineering and Non-Destructive Testing, 2015)
Заглавие с титульного экрана